2021
DOI: 10.1111/petr.14044
|View full text |Cite
|
Sign up to set email alerts
|

Large for size in pediatrics liver transplant using left lateral segment grafts: A single center experience

Abstract: Background There are still controversies in using the large left lateral segment in pediatrics LT, with the possibility of the problem of LFS grafts, and the use of monosegmental or reduced liver grafts in small infants. This study aimed to evaluate our experience with LFSG in pediatrics LT. Methods A cohort retrospective analysis was conducted including pediatric recipients who underwent LT between January 2011 and October 2019. We compared recipients with GRWR ≥ 4% (LFS) vs GRWR < 4% as an average for size g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…27,28 In pediatric LDLT, LFS grafts reportedly lead to early graft dysfunction. 29 In the present study, a GRWR > 5 was found to be an independent risk factor for PS, but not the age of the donor. 30,31 In pediatric LDLT in Japan, a GRWR > 4 was reported to be an independent risk factor.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…27,28 In pediatric LDLT, LFS grafts reportedly lead to early graft dysfunction. 29 In the present study, a GRWR > 5 was found to be an independent risk factor for PS, but not the age of the donor. 30,31 In pediatric LDLT in Japan, a GRWR > 4 was reported to be an independent risk factor.…”
Section: Discussioncontrasting
confidence: 50%
“…In pediatric LDLT, LFS grafts reportedly lead to early graft dysfunction 29 . In the present study, a GRWR >5 was found to be an independent risk factor for PS, but not the age of the donor 30,31 .…”
Section: Discussionsupporting
confidence: 40%
“…This, in turn, will increase intrahepatic vascular resistance, decreasing portal blood flow and increasing the incidence of PVT after transplantation. As a result, it is not surprising that many studies, including our own, have reported PVT occurring more frequently within the first week after the transplant 4,11,12 and some authors have suggested using smaller grafts and delaying abdominal wall closure in low weight patients after LT 7,11,16–19 …”
Section: Discussionmentioning
confidence: 83%
“…This, in turn, will increase intrahepatic vascular resistance, decreasing portal blood flow and increasing the incidence of PVT after transplantation. As a result, it is not surprising that many studies, including our own, have reported PVT occurring more frequently within the first week after the transplant 4,11,12 and some authors have suggested using smaller grafts and delaying abdominal wall closure in low weight patients after LT. 7,11,[16][17][18][19] Studies by Neto et al 11 and de Magnee et al 20 showed that the use of vascular grafts was associated with a greater risk of posttransplant PVT. Nevertheless, in this study, only one vascular graft was used and thus we were unable to determine its possible role in to be associated with PVCs in general and not with PVT specifically.…”
Section: Discussionmentioning
confidence: 99%
“…However, many authors suggest that a good surgical strategy for bigger grafts leads to no inferior results. Also, they have denied the major concerns of delayed abdominal closure, such as the increased possibility of a local wound and abdominal infections 19,20 . In conclusion, an underestimation of liver graft size and associated recipient risks should be considered by using a "one-to-one" rule.…”
Section: Discussionmentioning
confidence: 99%